Profile of Online Learning in Building Engineering Education Study Program During the COVID-19 Pandemic - Heri Suryaman; Kusnan; Husni Mubarok (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
This study attempts to discuss the profile of brave learning during the COVID-19 pandemic: (1) validity and reliability of instrument; (2) interesting learning for students; (3) implementation of learning; (3) strengths and weaknesses of learning; and (4) application that matches the learning profile and the condition of the existing internet network. The participant of this study were students and lecturers supporting courses in the Building Engineering Education study program. Data collection uses quantitative and qualitative methods. The questionnaire was given by online to 67 students and 6 lecturers. The result of this research shows that (1) questionnaire instruments have been tested as valid and reliable; (2) online learning is not all interesting; (3) online learning has been implemented, but some lecturers have problems when making corrections, the condition of the internet network in some regions is not smooth enough to be an obstacle for students to access applications; (4) using of the application adjusts the online learning profile and the condition of the internet network in the area. The conclusion reveals that applications of online learning must be easily accessible, used, interesting, and needs to be combined with several applications to provide the perfection of delivery and acceptance of material in teaching and learning activities.